Associations of blood metals with liver function: Analysis of NHANES from 2011 to 2018. (March 2023) - Li, Wenjie; Li, Xinyan; Su, Jing; Chen, Han; Zhao, Ping; Qian, Haisheng; Gao, Xin; Ye, Qiang; Zhang, Guoxin; Li, Xuan
Abstract: Background: Heavy metals have been reported to affect liver function. However, there is currently little and inconsistent knowledge about the effects of combined and individual blood metals on specific parameters of liver function in the general population. Hence, this study aimed to elucidate their associations. Methods: Data from National Health and Nutrition Examination Survey (NHANES) 2011–2018 were used in this cross-sectional study. Multivariate linear, and a quantile-based g-computation (qgcomp) were applied to explore the associations between blood metals [mercury (Hg), manganese (Mn), lead (Pb), cadmium (Cd), selenium (Se)], alone and in combination, and liver function parameters [alanine transaminase (ALT), aspartate transaminase (AST), ALT/AST, alkaline phosphatase (ALP), gamma-glutamyl transferase (GGT) and serum total bilirubin (TBIL)]. Results: A total of 15, 328 were included. Multivariate linear models indicated that liver function was significantly associated with blood heavy metals. The most significant relationship was found between Se and AST (β 5.09, 95%CI (3.28, 6.91), p＜0.001), Mn and ALT (β 1.24, 95%CI (0.57, 1.91), p＜0.001). Furthermore, the qgcomp analysis showed that the combination of five blood metals was positively associated with AST, ALT, GGT, TBIL and HSI. Cd contributed the most to the correlation of AST (weight = 0.447), Se contributed the most to the association of ALT (weight = 0.438) and HSI (weight = 0.570), Pb contributed the most to the association of GGT (weight = 0.421) and Hg contributed the most to the correlation of TBIL (weight = 0.331). Conclusions: Blood heavy metal levels were significantly associated with liver function parameters. Further studies are required to clarify the relationship between heavy metals and liver function. Graphical abstract: Image 1 Highlights: Blood Hg, Mn, Pb, Cd and Se were significantly associated with liver function parameters individually. Se is positively associated with AST, Mn is positively associated with ALT. The combination of Hg, Mn, Pb, Cd and Se is positively correlated with ALP, ALT, AST, AST/ALT, GGT and TB.